Pengaruh Partisipasi Masyarakat, Profesionalisme, dan Optimalisasi Pengelolaan Aset Desa Terhadap Pendapatan Asli Desa (Studi pada Desa dan Kelurahan di Kecamatan Kota Sumenep) - Sri Damayanti Wulandari; Astri Furqani (Jurnal Multidisiplin Madani, 2022)
Efforts to increase Village Original Income are managing village assets professionally, utilizing village assets optimally and requiring community participation support. The fact is that there are still some villages whose asset inventories are less than optimal, thus triggering conflicts over village asset problems in the future. The type of data in this research is quantitative data, the data source of this research is primary data. The sample of this research was conducted in 12 villages, 4 sub-districts. The results of this study indicate that Community Participation and Optimization of Village Asset Utilization have no significant effect on Village Original Income. While the Professionalism of Village Asset Management has a positive effect on Village Original Income. Thus there is only one variable that has a positive and significant effect on Village Original Income.